Historical Overview of Opportunism of the Russian Foreign Policy towards Serbia and its Reflection on the Western Balkans / Historijski presjek oporunizma ruske vanjske politike prema Srbiji i njegova refleksija na Zapadni Balkan (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
The paper elaborates on the history of the Russian foreign policy towards Serbia, with special emphasis on the national interests of the Russian state, which, in addition to undoubtedly strong traditional cultural and historical ties between the two Orthodox nations, still significantly guide Russian policies towards Serbia. In other words, the subject of the paper is numerous examples and evidence of opportunism in relation between these countries and its reflection on the countries of the Western Balkans. Namely, starting from the nineteenth century onwards, Russia has emerged as a strong foreign policy partner of Serbia, thus expanding its influence on other Western Balkans countries. In this way, Russia, as a great political power, capitalizing on its own power and strong ideological, historical and cultural ties, uses Serbia to strengthen influence in the region and beyond. Starting from the historical insight in this relationship, the paper focuses on the tendency to present opportunism and pragmatism of the Russian foreign policy, guided exclusively by the Russian national interests, which is visible, both from historical perspective, and in the last twenty years. The relationship between Russia and Serbia is presented through the military, economic and diplomatic cooperation.
Keywords: opportunism; foreign policy; Russia; Serbia; Western Balkans